EKSTRAKSI DAN FRAKSINASI FOSFOLIPID DARI LIMBAH PENGOLAHAN MINYAK SAWIT [Extraction and Fractionation of Phospholipids from the Waste of Palm Oil Processing] - Teti Estiasih; Kgs . Ahmadi; Fithri Choirun Nisa; Ahmad Diaul Khuluq (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
This research aimed to extract and fractionate phospholipids from the most potential source of phospholipids of the waste of palm oil processing i.e. palm pressed fiber, sludge, and spent bleaching earth (adsorbent). The extraction process was performed by using chloroform-methanol, followed by polar lipid separation by solubilization in choloroform (to eliminate neutral lipid) and methanol (to extract phospholipids). Fractionation was performed based on the solubility in ethanol and acetone. There were 5 phospholipd fractions obtained, i.e. crude phospholipids (without fractionation), ethanol soluble, ethanol insloluble, ethanol soluble-acetone soluble, and ethanol soluble-acetone insoluble fractions. Each fraction was characterized for phospholipid composition and fatty acid profile. The result showed that palm pressed fiber had the highest content of phospholipids of 10,222.19 ppm. Extraction and separation of phospholipids from palm pressed fiber produced phospholipids with a purity of 61.67%. Phospholipids found in palm pressed fiber were phosphatidylinositol (PI), phosphatidylcholine (PC), phosphatidyletanolamin (PE), phosphatidylglycerol (PG), diphosphatidylglyerol (DPG), and phosphatidic acid (PA), while the impurities consisted of fatty acids and neutral lipids. Oleic acid is the most dominant fatty acid ini crude palm pressed fiber phospholipids. Fractionation increased the purity of phospholipids. Different phospholipids fractions showed different phospholipid composition and fatty acid profile. Ethanol soluble fraction had more PI, PC, PG, and PA, but less PE and DPG as compared to crude phospholipids. The ratio of PC to PE also increased after ethanol fractionation. The amount of more non polar phospholipids (PG, DPG, PA) were less in ethanol soluble-acetone insoluble fractions compared to ethanol soluble-acetone soluble fraction. The solubilization in ethanol increased total unsaturated fatty acids in ethanol soluble fractions, meanwhile the distribution of unsaturated and saturated fatty acid in ethanol soluble-acetone soluble and ethanol soluble-acetone insoluble was similar.